Regulation of heme biosynthesis via the coproporphyrin dependent pathway in bacteria - Aftab, Hadia; Donegan, Rebecca K. (Frontiers in Microbiology, 2024)
Heme biosynthesis in the Gram-positive bacteria occurs mostly via a pathway that is distinct from that of eukaryotes and Gram-negative bacteria in the three terminal heme synthesis steps. In many of these bacteria heme is a necessary cofactor that fulfills roles in respiration, gas sensing, and detoxification of reactive oxygen species. These varying roles for heme, the requirement of iron and glutamate, as glutamyl tRNA, for synthesis, and the sharing of intermediates with the synthesis of other porphyrin derivatives necessitates the need for many points of regulation in response to nutrient availability and metabolic need. In this review we examine the regulation of heme biosynthesis in these bacteria via heme, iron, and oxygen species. We also discuss our perspective on emerging roles of protein-protein interactions and post-translational modifications in regulating heme biosynthesis.